KERAGAMAN TUMBUHAN PAKU SEBAGAI PENDUKUNG OBJEK WISATA DI HUTAN WISATA ALAM OELUAN, TIMOR TENGAH UTARA - Ite Morina Yostianti Tnunay; Dicky Frengky Hanas (Saintek Lahan Kering, 2020)
Fern (Pteridophyta) is diverse and very easy to find include in Oeluan Natural Tourism Forest. However, this information was very limited even though fern is very potential can be a tourism support in Oeluan Natural Tourism Forest. This research aimed to inventory fern in Oeluan Natural Tourism Forest. The result showed that there are 17 ferns spesies from 8 family, are Aspleniaceae, Davalliaceae, Nephrolepidaceae, Polypodiaceae, Psilotacea, Pteridaceae, Tectariaceae, dan Thelypteridaceae. Polypodiaceae is dominant family in Oeluan Natural Tourism Forest.